2018
DOI: 10.1109/jstars.2018.2870650
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance Evaluation of Pixel-Level and Decision-Level Data Fusion of Landsat 8 OLI, Landsat 7 ETM+ and Sentinel-2 MSI for Crop Ensemble Classification

Abstract: Crops mapping unequivocally becomes a daunting task in humid, tropical, or subtropical regions due to unattainability of adequate cloud-free optical imagery. Objective of this study is to evaluate the comparative performance between decision-and pixel-levels data fusion ensemble classified maps using Landsat 8, Landsat 7, and Sentinel-2 data. This research implements parallel and concatenation approach to ensemble classify the images. The multiclassifier system comprises of Maximum Likelihood, Support Vector M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Sentinel is a series of satellites launched by ESA Copernicus [45]. Among them, Sentinel-2 is a series of optical satellite that contains two satellites--Sentinel-2A and Sentinel-2B [46]. In this paper, Sentinel-2A (S2A) products are downloaded through the ESA Copernicus data sharing website ().…”
Section: Methodsmentioning
confidence: 99%
“…Sentinel is a series of satellites launched by ESA Copernicus [45]. Among them, Sentinel-2 is a series of optical satellite that contains two satellites--Sentinel-2A and Sentinel-2B [46]. In this paper, Sentinel-2A (S2A) products are downloaded through the ESA Copernicus data sharing website ().…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of agricultural land cover mapping is basically positively correlated with the number of multitemporal images, Pax et al [10] found that with the increase in the number of time-series images, the estimation accuracy of land area in agricultural areas in Egypt become higher. In order to obtain sufficient cloud-free remote sensing data in humid, tropical, or subtropical regions, Useya and Chen [11] fuse multitemporal Landsat 8, Landsat 7, and Sentinel-2 data, and obtain more accurate crop maps in Zimbabwe. However, in the critical stages of crop growth, the subtle differences in phenology often have important indications for crop production, such as: the flowering of canola or the tillering stage of transplanted rice.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that optical remote sensing data can be used to produce maps with high spatial and spectral resolutions [4] and are effective for gathering various types of biomass information, such as leaf chlorophyll content [5] and leaf area index (LAI) [6]. Indeed, Landsat series data have proven effective for identifying crop types with a high level of accuracy [7,8], and red-edge and shortwave infrared reflectance data are useful for Within this framework, the main objective of the present study was to evaluate the potential of ASNARO-2 data for crop-type classification using machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%